Day 3 Wed, November 11, 2015 2015
DOI: 10.2118/177711-ms
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Fines and their Correlation to Reported Oil Recovery

Abstract: Rock Type: Chalk, Limestone and Dolostone • Coreplug Type: Outcrop and Reservoir Coreplug • Flooding Type: Spontaneous imbibition and water flooding experiment • EOR Strategy: Low salinity, Smart waterfloods and Advanced Ion Management • Rock Origin: Middle East, North Sea and United StatesFurthermore a good correlation was observed between the amount of produced fines and the reported amount of oil recovery. Herein it was observed that production of fines increased significantly when the composition of inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Spontaneous formation of water-in-oil dispersions occurred when salinity of the brine was below 2000 ppm, in agreement with the work of Emadi and Sohrabi (2013). Chakravarty et al (2015aChakravarty et al ( , 2015bChakravarty et al ( , 2015c suggested that mobile fines formed in a pore space during smart water flooding may lead to emulsion formation, which enhances the mobility of the oil phase and therefore increases the displacement efficiency. A mixture of fines, model oil and deionized water was studied in these experiments.…”
Section: Emulsion Formation At the Brine-oil Contactssupporting
confidence: 83%
See 2 more Smart Citations
“…Spontaneous formation of water-in-oil dispersions occurred when salinity of the brine was below 2000 ppm, in agreement with the work of Emadi and Sohrabi (2013). Chakravarty et al (2015aChakravarty et al ( , 2015bChakravarty et al ( , 2015c suggested that mobile fines formed in a pore space during smart water flooding may lead to emulsion formation, which enhances the mobility of the oil phase and therefore increases the displacement efficiency. A mixture of fines, model oil and deionized water was studied in these experiments.…”
Section: Emulsion Formation At the Brine-oil Contactssupporting
confidence: 83%
“…Increase in emulsion formation and better emulsion stability was observed with increasing the amount of fines (Arshad et al, 2017). This study confirmed the results of Chakravarty et al (2015aChakravarty et al ( , 2015bChakravarty et al ( , 2015c) that the distilled water emulsifies better than the seawater when synthetic oils are involved. However, a North Sea crude oil formed equal or larger amounts of emulsions with seawater than with distilled water.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…▪ Prediction of thermal properties and phase behavior of aqueous electrolyte systems (Thomsen et al, 1996). Over the past almost four decades, the extended UNIQUAC model has been further enhanced, extended, parameterized, and applied to various aqueous electrolyte systems and engineering applications (Aronu et al, 2011;Arrad et al, 2016Arrad et al, , 2017Arshad et al, 2016Arshad et al, , 2017Awan et al, 2010;Barzegar-Jalali et al, 2020;Bonalumi et al, 2016;Chakravarty et al, 2015bChakravarty et al, , 2015aChokradjaroen et al, 2012;Christensen & Thomsen, 2003Corrêa et al, 2023;Corrêa, Hao, et al, 2022;Darde et al, 2009Darde et al, , 2011Darde, Maribo-Mogensen, et al, 2012;Eftekhari et al, 2017;Faramarzi, Kontogeorgis, et al, 2009;Faramarzi, Kontogorgis, et al, 2009;Figueroa et al, 2016;Fosbøl et al, 2009aFosbøl et al, , 2009bFosbøl et al, , 2013García et al, 2005bGarcía et al, , 2006bGaspar, Arshad, et al, 2014;Gaspar et al, 2016;Gomis et al, 2022;Haghtalab & Peyvandi, 2012;Hashemi et al, 2020;Hingerl et al, 2014;Iliuta et al, 2000Iliuta et al, , 2002Kontogeorgis et al, 2022;Kovalenko et al, 2011;…”
Section: Introductionmentioning
confidence: 99%